Advanced chipless RFID : imaging 60 GHz MIMO/ML detection /: imaging 60 GHz MIMO/ML detection. (2016) - Karmakar, Nemai Chandra, 1963-; Zomorrodi, Mohammad, 1973-; Divarathne, Chamath, 1983-
No abstract available